COMPARATIVE EFFICACY AND SAFETY OF BIOLOGIC THERAPIES IN CHRONIC RHINOSINUSITIS WITH NASAL POLYPS: A SYSTEMATIC REVIEW AND NETWORK META-ANALYSIS - Jurayev J.A.,; Isaeva Z.A., (JOURNAL OF NEW CENTURY INNOVATIONS, 2026)
Abstract: Chronic rhinosinusitis with nasal polyps (CRSwNP) is a chronic inflammatory condition that significantly affects quality of life through persistent nasal obstruction, impaired smell, and recurrent sinus infections. Biologic therapies targeting type-2 inflammatory pathways have emerged as effective treatment options for patients with severe or refractory disease. However, direct head-to-head randomized controlled trials comparing biologic agents are limited. This study aimed to evaluate and rank the efficacy and safety of available biologics for CRSwNP using a systematic review and network meta-analysis. A comprehensive literature search was conducted in PubMed, Embase, Web of Science, and the Cochrane Library. Randomized controlled trials evaluating biologics in adult patients with CRSwNP were included. The primary outcomes included nasal polyp score (NPS), Sino-Nasal Outcome Test-22 (SNOT-22), University of Pennsylvania Smell Identification Test (UPSIT), nasal congestion score (NCS), and adverse events (AEs). Nine randomized controlled trials involving 1,190 patients were included, comparing three biologics—dupilumab, omalizumab, and mepolizumab—with placebo. Network meta-analysis demonstrated that dupilumab showed the highest efficacy across most outcomes, including NPS, SNOT-22, UPSIT, and NCS. Omalizumab ranked second for several symptom-related outcomes, while mepolizumab ranked second in reducing NPS but showed the highest probability of adverse events. Overall, dupilumab appears to provide the most effective and favorable treatment profile for CRSwNP, followed by omalizumab. These findings may guide clinicians in selecting optimal biologic therapy for patients with severe CRSwNP.